Study of natural insulation materials and compared it with no insulation building. (2021) - Hasan, Shaheen; Khan, Sabah; Akhtar, Iram; Kirmani, Sheeraz
Abstract: India is undergoing energy deficit for past two decades in power supply, both for required energy supply as well as peak load demand. The problem is intense during peak demand or in summer season and essential to plan load shedding by several plants to secure supply grid. So, now sustainability has become a discourse topic to save environment. The present environment is a sign of efficiency of building construction and industrial behavior, i.e. the way of resources used by them e.g. water consumption, energy use, emission of harmful gases and other factors. Building construction is the only sector to consume about 40% of total generated energy of India. Environment is directly and indirectly influenced by building operation and (material) construction, so now focus on applying effective material to save both environment and energy. Utilization of various bio-degradable insulation materials in building which enhance building strength, provides good human comfort, saves energy and environment. The most important aspect of this insulation material is its performance i.e. regularly provides the resistance to heat flow. It helps in reduction of energy consumption around 30–35% of energy and proportionate reduction of carbon di-oxide emission.